The Analysis of Bank Soundness Level by Using RGEC (Risk Profile, Good Corporate Governance, Earnings and Capital) Method in Three State-Owned Banks in Indonesia in the Period of 2011-2015 - Ine Rahmadania Saldianovitta (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This study aims to analyze the bank soundness level of 3 most popular commercial state-owned banks in Indonesia, namely: PT Bank Rakyat Indonesia Tbk, PT Bank Mandiri (Persero )Tbk and PT Bank Negara Indonesia (Persero) Tbk using RGEC Method (Risk Profile, Good Corporate Governance, Earnings and Capital). The bank soundness level was measured through some financial ratios such as NPL, IRR, LDR, LAR, ROA, ROE, NIM, OEF and factors of Good Corporate Governance (GCG) on RGEC Method. The type of this research in this study is quantitative descriptive and the data of this research were collected from the annual reports of each bank from the period between 2011 and 2015. The data were analyzed using MANOVA, ANOVA and Kruskall- Wallis methods in SPSS software. The findings of this research show that there is a significant difference on the Risk profile factors among BRI, Mandiri and BNI. The following factor, namely earning show significant differences as well. However, the capital factor and the GCG factors of those three banks do not indicate any significant difference.Keywords: Bank Soundness Level, RGEC Method, State-owned Banks